Factors affecting the prevalence of ticks in cattle and acaricidal activity of Nicotiana tabacum extracts - ULLAH, N.; AKHTAR, R.; LATEEF, M.; JAN, S. U.; ZAHID, B.; DURRANI, U. F. (Journal of the Hellenic Veterinary Medical Society, 2019)
The present study was designed to determine factors affecting the prevalence of ticks (Hyalomma and Rhipicephalus) in cattle in district Loralai of Balochistan and to evaluate the acaricidal activity of chloroform and methanol extracts of tobacco (Nicotiana tabacum). A total of 670 cattle of different breeds, age and gender were examined for tick infestation with overall prevalence of 21.49% in Loralai. Friesian was more infected (26.15%) as compare to non-descriptive (22%) and Sahiwal (12.80%) breeds. Similarly, cattle less than one year old were most infected (27.90%) followed by those between 1-2 year (26.88%); the least prevalence was in cattle more than 2 years of age (19.34%). Higher prevalence was noticed in female cattle (21.98%) as compare to male cattle (16.92%). Three concentrations of (Nicotiana tabacum) (12.5mg/mL, 25mg/mL and 50mg/mL) were prepared in chloroform and methanol. The acaricidal activity of these extracts was determined by egg laying index and percentage inhibition of egg laying. The decline in egg laying index was significantly more by chloroform extract (10.048%, 17.378% and 25.143%) as compare to methanol extract (6.367%, 13.152% and 20.827%). Hatchability of eggs in chloroform extract was less than that in methanol extract (67.5%, 43.5% 17% and 77.5%, 47.5% and 23%) respectively. We concluded that the prevalence of ticks in cattle is affected by their age, breed and gender and that chloroform extract of Nicotiana tabacum is more acaricidal as compared to the methanol extract.